Promotion of Interaction Between University-Industry-National R&D Labs-National Academies An Approach Paper - (:unkn) unknown (Planning Commission, 1996)
The Approach Paper on promoting interaction between universities, industries, national R&D laboratories, and national academies emphasizes the critical need for collaborative frameworks to strengthen India’s innovation ecosystem. It identifies key stakeholders—including industry, academic institutions, R&D organizations, and national academies—highlighting their complementary roles and the barriers that hinder effective collaboration, such as trust deficits, confidentiality concerns, bureaucratic hurdles, and autonomy conflicts. The paper outlines strategies for enhancing interaction, including incentivizing industry investment in R&D, establishing national R&D funds, streamlining tax benefits, and creating flexible organizational structures. Models such as sandwich courses, joint R&D projects, and Science Parks are proposed to facilitate practical collaboration. Overall, the paper advocates for a comprehensive policy and cultural shift to integrate academic knowledge, industrial needs, and applied research, thereby driving technological innovation and national development.
The Standing Committee on Industry-Institution Interaction Planning Commission Government Of India New Delhi
The Standing Committee on Industry-Institution Interaction Planning Commission Government Of India New Delhi
Keywords: University Industry Collaboration; R&D Interaction; National Academies; Innovation Policy; Technology Transfer; Stakeholder Engagement; Research Funding; Science Parks; Technical Education; Industrial Partnerships